การศึกษาเปรียบเทียบผลสัมฤทธิ์ทางการเรียนโดยใช้บทเรียนคอมพิวเตอร์ช่วยสอนผ่านเว็บกับการสอนปกติ เรื่อง เทคนิคการค้นคืนสารสนเทศเบื้องต้น - วรัญญานุไกร, สมชาย (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2015)
บทคัดย่อ การวิจัยครั้งนี้มีความมุ่งหมายเพื่อเปรียบเทียบผลสัมฤทธิ์ทางการเรียนหลังเรียน เรื่อง เทคนิคการค้นคืนสารสนเทศเบื้องต้น ของนิสิตโดยใช้บทเรียนคอมพิวเตอร์ช่วยสอนผ่านเว็บกับการสอนปกติ และความคิดเห็นของนิสิตที่มีต่อบทเรียนคอมพิวเตอร์ช่วยสอน กลุ่มตัวอย่างเป็นนิสิตระดับปริญญาตรี ชั้นปีที่ 3 วิชาเอกบรรณารักษศาสตร์และสารสนเทศศาสตร์ และวิชาเอกภาษาเพื่ออาชีพที่ลงทะเบียนเรียนวิชา ดังกล่าว ปีการศึกษา 2550 และสุ่มอย่างง่ายเพื่อแบ่งเป็นกลุ่มควบคุม และกลุ่มทดลอง โดยวิชาเอกบรรณารักษศาสตร์และสารสนเทศศาสตร์ จำนวน 22 คน เป็นกลุ่มควบคุม วิชาเอกภาษาเพื่ออาชีพ จำนวน 26 คน เป็นกลุ่มทดลอง เครื่องมือที่ใช้ในการวิจัยเป็นบทเรียนคอมพิวเตอร์ช่วยสอนผ่านเว็บ เรื่อง เทคนิคการค้นคืนสารสนเทศเบื้องต้น ซึ่งผู้วิจัยสร้างขึ้น และแบบทดสอบวัดผลสัมฤทธิ์ทางการเรียน การทดลองครั้งนี้ กลุ่มทดลองเรียนโดยใช้บทเรียนคอมพิวเตอร์ช่วยสอนผ่านเว็บ ส่วนกลุ่มควบคุมเรียนจากการเรียนการสอนปกติในชั้นเรียน เมื่อเรียนจบแล้วทดสอบด้วยแบบทดสอบวัดผลสัมฤทธิ์ทางการเรียนทั้งสองกลุ่ม แล้วนำผลที่ได้มาวิเคราะห์โดยทดสอบค่า t (t-test) ผลการวิจัยพบว่า 1) ผลสัมฤทธิ์ทางการเรียนของกลุ่มเรียนโดยบทเรียนคอมพิวเตอร์ช่วยสอนผ่านเว็บ ไม่แตกต่างจากกลุ่มเรียนโดยวิธีสอนปกติ 2) นิสิตมีความคิดเห็นต่อบทเรียนคอมพิวเตอร์ช่วยสอนผ่านเว็บ เรื่อง เทคนิคการค้นคืนสารสนเทศเบื้องต้นอยู่ในระดับมาก Abstract The purpose of this study was twofold. Firstly, this study compared the learning achievement of students who studied the course Introduction to Information Retrieval with two different teaching methods: lecture plus web-based instruction lesson and lecture-based instruction. Secondly, the study examined student opinions towards the web-based instruction lessons. Purposive sampling was used to draw a sample from the students who were studying in year 3 at the Faculty of Humanities. The control group comprised 22 students in library and information science. The experimental group comprised 26 students in Language for career. The research instruments used were web-based instruction lessons developed for the course Introduction to Information Retrieval and achievement tests. The experimental group studied these lessons with lecture plus web-based instruction method. The controlled group studied the lessons taught by lecturing only. The data was analyzed by using T-test. The study results show that 1) There was no significant difference between both groups in the achievement and retention test scores so the web-based instruction can be used to replace the traditional teaching method and to increase retention test scores in specific text; and 2) Students opinion towards the web-based instruction lessons developed for this course was at high level of satisfaction.